Penyusunan Sistem Pengembangan Karyawan Melalui Pelatihan dengan Pendekatan Appreciative Inquiry - Edwarsyah Edo; Seger Handoyo; Maria Eko Sulistyowati (INSAN Jurnal Psikologi dan Kesehatan Mental, 2019)
One of the biggest challenges in the oil and gas industry in the upstream sector is sustainable of oil and gas exploration and exploitation activities to keep the field in continuous production. Successful exploration and production activities cannot be separated from the ability and management of human resources in the company. The company requires professional and high qualifications workforce in managing upstream oil and gas business activities that have characteristics of high capital, risk and technology intensives. This research was conducted with the aim of compiling an employee development system through training with the Appreciative Inquiry approach. The research method is qualitative using the stages of 4D Appreciative Inquiry. The results showed that the Appreciative Inquiry approach could bring out the positive strengths and core-values that exist within the organization, and make a commitment from the organization to do better in terms of employees training and development.